Exploration of fever characteristics in parturients under continuous temperature monitoring during labor analgesia and analysis of the impact on maternal and neonatal outcomes: an observational study - Li, Xia; Ma, Junli (Frontiers in Global Women's Health, 2025)
ObjectiveBy continuous core temperature monitoring, this study aims to explore the patterns of fever in parturients receiving labor analgesia and analyze its impact on both the maternal and neonatal.MethodsNon-invasive temperature monitoring sensors (iThermonitor705) and labor analgesia temperature management system were used to collect temperature data from parturients. Based on the presence or absence of fever during the peripartum period, the subjects were divided into a fever group and a non-fever group. Maternal temperature data during the peripartum period, along with maternal and neonatal demographic and clinical characteristics, were collected.ResultsAmong the parturients receiving labor analgesia, 25.9% (43/166) developed a fever during the peripartum period. Of these, 25.6% (11/43) experienced their first fever after delivery, all occurring within 2 h after delivery. Compared to the non-fever group, the fever group had longer durations of the first stage of labor, total labor duration, and epidural analgesia. Additionally, the fever group had a higher rate of meconium-stained amniotic fluid (grade III), used more analgesics, and had a higher rate of antibiotic use. However, no significant differences in adverse maternal and neonatal outcomes were observed between the two groups.ConclusionFever can occur not only during labor but also for the first time after delivery. Although fever during the peripartum period increases the rate of maternal exposure to antibiotics, there were no significant differences in maternal or neonatal outcomes between the two groups.